What can a dissident body do in capoeira? - Schimith, Mateus; Rodrigues, Alexsandro (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This article investigates how LGBTQIA+ capoeira practitioners experience gender and sexual performativity, analyzing the intersections of sexuality, race, class, and precarity. In its third stage, the research employed structured interviews with four LGBTQIA+ capoeiristas who teach in their groups, located in different Brazilian states. Analysis of the accounts shows that these bodies experience specific forms of exclusion and silencing, being pressured to conceal their identities as a survival strategy. Moreover, even though rooted in an ancestral matrix of resistance, capoeira reproduces hegemonic norms that hinder the recognition and advancement of dissident individuals. In conclusion, strengthening dissident performativity in capoeira depends on creating more plural spaces and confronting the symbolic and material hierarchies that sustain historical exclusions. By engaging with present urgencies, capoeira practice may reaffirm its libertarian potential, provided it opens space for the diversity of bodies and knowledges.